Synthesis of Biodiesel From Rubber Seed Oil with Acid and Base Activated Natural Zeolite Catalyst - Tiamina Nasution; Akhir Mauludin Pulungan; Yuli Asih Wiliranti; Junifa Layla Sihombing; Ahmad Nasir Pulungan (Universitas Negeri Medan, 2019)
In this study, biodiesel synthesis was carried out using Z-AH and Z-OH Zeolite catalysts to obtain a cheaper and environmentally friendly process. The catalysts were prepared from Sarulla Indonesian natural zeolite (Z-AS) through a chemical activation process with certain HCl 3 M and NaOH 2 M, then calcined at 500°C with Nitrogen gas for 4 hours to obtain Z-AH ang Z-OH catalyst. The catalysts were characterized by FT-IR and XRD. The conversion of rubber seed oil into biodiesel was carried out at temperature of 30 oC, 60 oC and 90 oC. The ratio of methanol: rubber seed oil is 6: 1 (v / v) and the catalyst concentration used is 1% wt. The XRD and FTIR data show that Z-AS activation increases the crystallinity of zeolite and does not damage the zeolite skeletal structure.The Z-AH catalyst has a better catalytic activity than the Z-OH catalyst with the conversion value of the biodiesel product obtained at 69.79%.